The Institutional Provision for Anti-Crisis Regulation of the Country’s Economic Security - Kondratenko Nataliia O.; Dobryanskyy Oleg I. (Bìznes Inform, 2023)
The article identifies problems and prospects of institutional provision for anti-crisis regulation of economic security of Ukraine. It is noted that the current level of economic security of Ukraine, complicated by the wartime, requires new approaches to institutional provision in terms of crisis management and regulation capable of solving the issue of reducing the level of corruption and shadowing the economy, which will significantly affect the implementation of our country’s intention to become a member of the European Union. It is noted that institutional provision for anti-crisis regulation of economic security of the country is considered as a complex and integrated system of socioeconomic development and provides for the implementation of appropriate measures (organizational, economic, technological, preventive, controlling, and protective), which are taken to neutralize the negative impact on the economic security of the State. It is determined that one of the main conditions for building an effective system of institutional provision for anti-crisis regulation of economic security of the country is the introduction of regular monitoring of the implementation of previously adopted decisions, formation of a dynamic information structure of institutional regulation of the national economy and elimination of existing administrative barriers and restrictions. It is concluded that one of the important conditions for the formation of an efficient system of institutional provision for anti-crisis regulation of economic security of Ukraine is the use of modern management technologies in combination with the development of the institutional environment, which covers a set of important institutions, formal and informal institutions and institutional changes aimed at improving the qualitative characteristics of formal and informal institutions that already exist in the field of anti-crisis regulation of economic security. A system of institutional provision for anti-crisis regulation of economic security of the country has been proposed, which provides for the complexity of solving problems at all levels of management, optimization of anti-crisis measures and equalization of conditions for economic management and human life, which, in turn, will allow solving the issue of creating conditions for development of both business and social sphere.